The Effect of Profitability on Company Value with Dividend Policy as a Moderating Variable - Ida Ayu Nirma Prameswari (Jurnal Inovasi Akuntansi (JIA), 2024)
This research aims to provide empirical evidence of the influence of profitability on company value with dividend policy as a moderating variable. The population of this research is all consumer goods sector companies listed on the Indonesia Stock Exchange for the period 2017 – 2022. The sampling technique used was purposive sampling technique and obtained as many as114 number of observations. This study uses the Statistical Product and Service Solution (SPSS) program with Moderated Regression Analysis (MRA) as a tool to analyze the moderating effect of dividend policy on the sample tested. The results of the analysis provide evidence that profitability has a positive effect on company value. Furthermore, dividend policy is unable to moderate profitability on company value.